Learning Outcome Based Curricula Design for Total Quality in Engineering Education - Kulkarni, Sushma S. (Journal of Engineering Education Transformations, 2007)
Engineering Education in India is experiencing a phenomenal growth and this growth is supported by the fact that there is huge requirement of trained and skilled manpower in the country&all over the world. Total Quality management call provide the umbrella to transform the quantitative growth into qualitative growth in engineering education. One of the vital pillars on which TQM stands is customer satisfaction&to satisfy stakeholders ill education systems one of the significant factors is Teaching Learning process. In this paper it is suggested to strengthen Teaching Learning process by focusing on learning outcome based curriculum design. A systematic approach to outcome based curriculum development will lead to student assessment, based on defined learning outcome which will drive learning in students. All efforts in any Technical Education Institutes is to enhance learning ability of students so as to lead to 100% placement of students in premier organizations to achieve Total Quality in Engineering Education.